IFR uncovers profound but mostly reversible ischemia in CTOs and helps to optimize PCI results. Issue 4 (17th June 2020) - Kayaert, Peter; Coeman, Mathieu; Drieghe, Benny; Bennett, Johan; McCutcheon, Keir; Dens, Jo; Ungureanu, Claudiu; Zivelonghi, Carlo; Agostoni, Pierfrancesco; Bataille, Yoann; de Hemptinne, Quentin; Gevaert, Sofie; et al.
Abstract: Objectives: The study aimed to demonstrate through instant wave‐free ratio (iFR) measurements that myocardium distal to a chronic total occlusion (CTO) is ischemic, that ischemia is reversible by PCI, and that iFR assessment after PCI can be used to optimize PCI results. Background: The greatest benefit of revascularization is found in patients with low fractional flow reserve. In patients with CTOs, iFR measurement may be more appropriate to evaluate ischemia as it does not require maximal microvascular vasodilation, which may be hampered by microvascular dysfunction. Methods: The iFR was measured in 81 CTO patients, both pre‐ and post‐PCI in 63 patients, and only post‐PCI in the following 18 patients. A pressure wire pullback was performed post‐PCI if iFR ≤0.89. Results: The first 63 patients all had significant ischemia distal to the CTO with a median iFR of 0.33 [0.22; 0.44], improving significantly post‐PCI to a median iFR of 0.93 [0.89;0.96] ( p < .001). In the complete cohort, the median iFR post‐PCI was 0.93 [0.86;0.96] but still ≤0.89 in 23 patients (30%). 12 of these patients had further PCI optimization because of a residual focal pressure gradient on pullback, after which only two had a final iFR ≤0.89. Conclusions: In CTO patients with an indication for PCI, iFR consistently demonstrated profound myocardial ischemia. Successful PCI immediately relieved ischemia in 70% of patients. In the remaining 30% of cases, a manual iFR pullback proved helpful in guiding further optimization of the PCI result.